2014
DOI: 10.7202/1024668ar
|View full text |Cite
|
Sign up to set email alerts
|

Les étudiants sont-ils compétents pour évaluer la qualité des enseignements ?

Abstract: Cet article répond à cette question centrale : « Les étudiants sont-ils compétents pour évaluer la qualité des enseignements ? » en l’abordant selon deux angles distincts. Le premier a trait aux attitudes et représentations des différentes parties prenantes quant à cette question. Ces attitudes ne sont pas univoques bien qu’elles soient, en tendance, favorables à l’implication des étudiants dans les dispositifs d’évaluation des enseignements. Le second a trait à la validité de l’information ainsi récoltée. La … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 49 publications
4
8
0
1
Order By: Relevance
“…The literature review indicated that the majority of teachers do not question the role and relevance of student teaching assessment (Beran & Rokosh, 2009;Berthiaume et al, 2011;Detroz & Blais, 2012). The results of our study showed that just over two-thirds of the teachers surveyed (69.6%) agreed with the assessment of teaching by students.…”
Section: Perceptions Of Student Appreciation Of Teachingsupporting
confidence: 44%
See 2 more Smart Citations
“…The literature review indicated that the majority of teachers do not question the role and relevance of student teaching assessment (Beran & Rokosh, 2009;Berthiaume et al, 2011;Detroz & Blais, 2012). The results of our study showed that just over two-thirds of the teachers surveyed (69.6%) agreed with the assessment of teaching by students.…”
Section: Perceptions Of Student Appreciation Of Teachingsupporting
confidence: 44%
“…On the other hand, for some professors, the information collected from the students makes it difficult to obtain real insight into the quality of the course being taught (Berthiaume et al, 2011;Detroz & Blais, 2012;Younès & Romainville, 2012). Professors believed that student evaluations are unreliable, since they are not qualified to identify good teaching and the questionnaires are not valid instruments for assessing the quality of teaching (Bocquillon et al, 2017;Endrizzi, 2014;Gravestock & Gregor-Greenleaf, 2008).…”
Section: Professors' Perceptions Of Teacher Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Students are the only witnesses of the teaching; they are the only ones who can indicate whether the teacher's presentations are clear, whether the teacher's feedback helps them to progress, whether the teacher's strategies can promote student understanding [loose translation] [24] On the other hand, for some professors, the information collected from the students makes it di cult to obtain real insight into the quality of the course being taught [16,21,25]. Professors believed that student evaluations are unreliable, since they are not quali ed to identify good teaching and the questionnaires are not valid instruments for assessing the quality of teaching [17,[26][27].…”
Section: Professors' Perceptions Of Teacher Assessmentmentioning
confidence: 99%
“…tout le courant conflictualiste de la sociologie de l'éducation, notamment les travaux de Bourdieu et Passeron, 1964, 1970, et d'autres encore se penchent sur les effets simultanés de l' environnement des études et de l' expérience universitaire des étudiants (Blais et al, 1997;Coulon, 1997;Coulon et Paivandi, 2008;Frenay et al, 1998;Marton et Säaljö, 1976;Ramsden et Entwistle, 1981;Romainville, 2006Romainville, , 2013Wathelet et Vieillevoye, 2013). De nombreuses études ont examiné les visées de l' évaluation de l' enseignement par les étudiants (EEE), en rapport avec l'amélioration de l' enseignement et le développement professionnel des enseignants (Detroz et Blais, 2012;Dumont, Rochat, Berthiaume et Lanarès, 2012;Fontaine, 2009;Poissant, 1996 Cependant, elles comportent aussi quelques limites sur lesquelles il est instructif de s'arrêter. D'abord, elles s'appuient quasi uniquement sur des questionnaires : l' on s'intéresse particulièrement aux scores obtenus et la préoccupation, donc, est celle de la qualité et des effets des pratiques évaluatives sur la réussite ou l' échec scolaire des étudiants, réussite ou échec étant conçus de manière normative.…”
unclassified